Darrieus wind turbine prototype: dynamic modeling parameter identification and control analysis - Tobias, Pereira (2019)
This paper details the process required to develop a linear dynamic model and control of a Darrieus wind turbine equipped with a Permanent Magnet Synchronous Generator. The turbine is to be integrated in a smart grid for future installation in urban context. An active control system is integrated in such a way that, even in the presence of non-ideal phenomena and disturbances, optimal operation is achieved. For the class of linear (or linearized) systems such optimal control solution corresponds to the Linear Quadratic Regulator (LQR). A set of tests were performed on a wind tunnel, data was acquired allowing the application of well rooted identification techniques, leading to the deduction and validation of several low order dynamic models. Optimal control solutions were implemented to guarantee that close to ideal operational conditions are maintained. As such, efficiency is improved without jeopardizing the integrity of the wind turbine in a broad set of operational conditions.